(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2024)
The purpose of this study was to investigate the Patterns of brain dominance among secondary school Students, and their relationships with Statistical thinking, gender, grade, and specialization. A cluster sample of (280) students participated in the study. The Hemisphere Dominance Inventory and a Test of Statistical Thinking were used for collecting data. The results of the study revealed that left hemisphere dominance, followed by integrated hemisphere dominance, were the most common types among students. There were significant differences in brain dominance due to academic specialization variable, but no significant ones due to gender variable. The results also indicated that the Statistical thinking was correlated with left and integrated hemisphere, but not with right hemisphere; the mean of the right hemisphere subjects was significantly lower than left and integrated hemisphere subjects, and the mean of the integrated hemisphere subjects was lower than left hemisphere subjects in all Statistical thinking scores. These results highlight the importance of brain function in the statistical process for the secondary school Students.